Nosocomial COVID-19 infection: examining the risk of mortality. The COPE-Nosocomial Study (COVID in Older PEople). Issue 2 (October 2020) - Carter, B.; Collins, J.T.; Barlow-Pay, F.; Rickard, F.; Bruce, E.; Verduri, A.; Quinn, T.J.; Mitchell, E.; Price, A.; Vilches-Moraga, A.; Stechman, M.J.; Short, R.; et al.
Summary: Background: Hospital admissions for non-coronavirus disease 2019 (COVID-19) pathology have decreased significantly. It is believed that this may be due to public anxiety about acquiring COVID-19 infection in hospital and the subsequent risk of mortality. Aim: To identify patients who acquire COVID-19 in hospital (nosocomial COVID-19 infection (NC)) and their risk of mortality compared to those with community-acquired COVID-19 (CAC) infection. Methods: The COPE-Nosocomial Study was an observational cohort study. The primary outcome was the time to all-cause mortality (estimated with an adjusted hazard ratio (aHR)), and secondary outcomes were day 7 mortality and the time-to-discharge. A mixed-effects multivariable Cox's proportional hazards model was used, adjusted for demographics and comorbidities. Findings: The study included 1564 patients from 10 hospital sites throughout the UK, and one in Italy, and collected outcomes on patients admitted up to April 28 th, 2020. In all, 12.5% of COVID-19 infections were acquired in hospital; 425 (27.2%) patients with COVID died. The median survival time in NC patients was 14 days compared with 10 days in CAC patients. In the primary analysis, NC infection was associated with lower mortality rate (aHR: 0.71; 95% confidence interval (CI): 0.51–0.98). Secondary outcomes found no difference in day 7 mortality (adjusted odds ratio: 0.79; 95% CI: 0.47–1.31), but NC patients required longer time in hospital during convalescence (aHR: 0.49, 95% CI: 0.37–0.66). Conclusion: The minority of COVID-19 cases were the result of NC transmission. No COVID-19 infection comes without risk, but patients with NC had a lower risk of mortality compared to CAC infection; however, caution should be taken when interpreting this finding.